Lamellarly Stacking Porous N, P Co‐Doped Mo 2 C/C Nanosheets as High Performance Anode for Lithium‐Ion Batteries - Lyu, Fucong; Zeng, Shanshan; Sun, Zhifang; Qin, Ning; Cao, Lujie; Wang, Zhenyu; Jia, Zhe; Wu, Shaofei; Ma, Fei‐Xiang; Li, Minchan; Wang, Wenxi; Li, Yang Yang; et al. (Small (Weinheim an der Bergstrasse, Germany), 2019)
Layered stacking and highly porous N, P co‐doped Mo 2 C/C nanosheets are prepared from a stable Mo‐enhanced hydrogel. The hydrogel is formed through the ultrafast cross‐linking of phosphomolybdic acid and chitosan. During the reduction of the composite hydrogel framework under inert gas protection, highly porous N and P co‐doped carbon nanosheets are produced with the in situ formation of ultrafine Mo 2 C nanoparticles highly distributed throughout the nanosheets which are entangled via a hierarchical lamellar infrastructure. This unique architecture of the N, P co‐doped Mo 2 C/C nanosheets tremendously promote the electrochemical activity and operate stability with high specific capacity and extremely stable cycling. In particular, this versatile synthetic strategy can also be extended to other polyoxometalate (such as phosphotungstic acid) to provide greater opportunities for the controlled fabrication of novel hierarchical nanostructures for next‐generation high performance energy storage applications.